Predarea dreptului bisericesc în cadrul învățământului universitar clujean până la instaurarea comunismului - Perșa, Răzvan (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
Following the unification of Romania in 1918, the theological academic landscape underwent significant transformations, particularly with the introduction of Canon Law as a subject within the university curriculum. This development fostered a reevaluation of the relationship between State and Church. As the sole subject with theological content in the state university system, Canon Law maintained an interconfessional nature. In the context of Cluj university education, Canon Law was taught at both the Faculty of Law of the University of Cluj and the Theological Institute, which later evolved into the Romanian Orthodox Theological Academy of Cluj. Subsequently, due to the persistent efforts of Bishop Nicolae Ivan, the Theological Institute of Cluj was established on October 1, 1924, under the auspices of the Bishopric of Cluj. In addition to the financial challenges associated with such an undertaking, the Bishop of Cluj was tasked with assembling a university teaching staff that could support the cultural, theological, and spiritual aspects of the project. Within the Faculty of Law and the Faculty of Theology, distinguished interwar-period academics such as Petre Poruţiu, Vasile Sava, Valeriu Moldovan, and Iacob Lazăr were professors of Canon Law.